Association between cathepsins and benign prostate diseases: a bidirectional two-sample Mendelian randomization study - Cao, Hongliang; Liu, Bin; Gong, Kejian; Wu, Hao; Wang, Yishu; Zhang, Haiyang; Shi, Chengdong; Wang, Pengyu; Du, Hao; Zhou, Honglan; Wang, Song (Frontiers in Endocrinology, 2024)
The relationship between cathepsins and prostate cancer (PCa) has been reported. However, there is a lack of research on cathepsins and benign prostate diseases (BPDs). This study investigated the potential genetic link between cathepsins and BPDs through the utilization of Mendelian randomization (MR) analysis to determine if a causal relationship exists.Methods Publicly accessible summary statistics on BPDs were obtained from FinnGen Biobank. The data comprised 149,363 individuals, with 30,066 cases and 119,297 controls for BPH, and 123,057 individuals, with 3,760 cases and 119,297 controls for prostatitis. The IEU OpenGWAS provided the Genome-wide association data on ten cathepsins. To evaluate the causal relationship between BPDs and cathepsins, five distinct MR analyses were employed, with the primary method being the inverse variance weighted (IVW) approach. Additionally, sensitivity analyses were conducted to examine the horizontal pleiotropy and heterogeneity of the findings.The examination of IVW MR findings showed that cathepsin O had a beneficial effect on BPH (IVW OR=0.94, 95% CI 0.89-0.98, P=0.0055), while cathepsin X posed a threat to prostatitis (IVW OR=1.08, 95% CI 1.00-1.16, P=0.047). Through reverse MR analysis, it was revealed that prostatitis had an adverse impact on cathepsin V (IVW OR=0.89, 95% CI 0.80-0.99, P=0.035), while no favorable association was observed between BPH and cathepsins. The results obtained from MR-Egger, weighted median, simple mode, and weighted mode methods were consistent with the findings of the IVW approach. Based on sensitivity analyses, heterogeneity, and horizontal pleiotropy are unlikely to distort the results.This study offers the initial evidence of a genetic causal link between cathepsins and BPDs. Our findings revealed that cathepsin O was beneficial in preventing BPH, whereas cathepsin X posed a potential threat to prostatitis. Additionally, prostatitis negatively affected cathepsin V level. These three cathepsins could be targets of diagnosis and treatment for BPDs, which need further research.